In vitro study of effect of solvent on root canal retreatment - Oyama Kazumi Onaga Nagayama; Siqueira Evandro Luiz; Santos Marcelo dos (Fundação Odontológica de Ribeirão Preto, 2002)
The aim of this study was to assess the effectiveness of five different solvents: xylol, eucalyptol, halothane, chloroform and orange oil on softening gutta-percha in simulated root canals. One drop of solvent was placed into a reservoir made in a simulated canal whose channel was previously instrumented and filled with gutta-percha and N-Rickert sealer. After 5 min, softening was evaluated for each solvent by the penetration of a spreader while applying force with a 442 Instron apparatus to reach a depth of 5 mm. The results were analyzed statistically by the Kruskal-Wallis test. Xylol and orange oil were better in softening gutta-percha than the other solvents. There was no significant difference between xylol and orange oil, but these were statistically different from eucalyptol, halothane and chloroform (p<0.01).